Crawl [videorecording (DVD)] - Scodelario, Kaya, 1992-; Pepper, Barry, 1970-; Anderson, Ross, 1987- (Paramount, 2019)
When a hurricane hits her hometown, Haley ignores evacuation orders to search for her missing father. Finding him injured in the crawl space of their family home, the two become trapped by floodwaters. As time runs out to escape the storm, Haley and her father discover that the rising water level is the least of their fears.